1996
DOI: 10.1074/jbc.271.11.6298
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Expression of a Tandemly Repeated, Proline- and Glutamine-rich Amino Acid Motif on Hyphal Surfaces of Candida albicans

Abstract: cDNA sequences encoding a cell wall protein have been isolated from the opportunistic pathogen, Candida albicans, an organism that can cause serious disease in immunocompromised patients such as those with AIDS. The cDNA encodes a peptide that is largely composed of an acidic, repeated motif 10 amino acids in length that is rich in proline and glutamine residues. The cDNA gene product was found to be present on hyphal surfaces by immunofluorescence assays using monospecific antisera raised to the recombinant p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
175
0
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 162 publications
(185 citation statements)
references
References 77 publications
9
175
0
1
Order By: Relevance
“…Proline-rich proteins are important structural components of plant cell walls, but few such proteins have been identified in fungi. Recently, a gene encoding a putative proline-rich protein was isolated from another biotrophic fungus, E. graminis (Justesen et al, 1996) and proline-rich proteins have been identified in C. graminicola and Candida albicans (Nicholson et al, 1986;Staab et al, 1996). The proline-rich proteins (PRPs) and hydroxyproline-rich glycoproteins (HRGPs), found in plant cell walls characteristically have repetitive motifs, although these differ from those found in the CIH1 polypeptide.…”
Section: Discussionmentioning
confidence: 99%
“…Proline-rich proteins are important structural components of plant cell walls, but few such proteins have been identified in fungi. Recently, a gene encoding a putative proline-rich protein was isolated from another biotrophic fungus, E. graminis (Justesen et al, 1996) and proline-rich proteins have been identified in C. graminicola and Candida albicans (Nicholson et al, 1986;Staab et al, 1996). The proline-rich proteins (PRPs) and hydroxyproline-rich glycoproteins (HRGPs), found in plant cell walls characteristically have repetitive motifs, although these differ from those found in the CIH1 polypeptide.…”
Section: Discussionmentioning
confidence: 99%
“…It codes for the adhesin Hwp1p, which was detected in the cell wall of hyphae but never of blastoconidia. Likewise, the HWP1-transcript is only present after commitment to hyphal growth (Staab et al, 1996(Staab et al, , 1999.…”
Section: Introductionmentioning
confidence: 99%
“…Hyphal wall protein (Hwp1), a transglutaminase substrate which functions as an adhesin, is important for the pathogenesis of candidiasis (Staab et al, 1996(Staab et al, , 1999Sundstrom et al, 2002). HWP1 mRNA and protein are abundant in hyphae in vitro, and greatly reduced or undetectable in yeast forms (Staab et al, 1996(Staab et al, , 1999 Sharkey et al, 1999;Nantel et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…HWP1 mRNA and protein are abundant in hyphae in vitro, and greatly reduced or undetectable in yeast forms (Staab et al, 1996(Staab et al, , 1999 Sharkey et al, 1999;Nantel et al, 2002). Hypha-specific expression of Hwp1 extends to fungal growth in the host, as shown by the presence and absence of Hwp1 on hyphae and yeast, respectively, in candidiasis of the murine stomach (Sundstrom et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation